A ordem panteísta no indianismo de José de Alencar: uma incursão estético-filosófica - Rodrigo Vieira Ávila de Agrela (2015)
In Brazil, the relationship between art and nature was very common during the secong group of Brazilian Romanticism. The nature's feeling, in Afrânio Coutinho's (1969) words, became 'almost a religion', for the writers were fascinated by the majestic and potentially essential character of nature. This behavior can be perceived in the first romantics who, as said by Heine (1991), acted on a pantheistic instinct that even themselves could not assimilate. From this presupposition, this work's proposal is to trace a study on the harmony relationship between man and nature in the indianist novels 'O Guarani' (1857), 'Iracema' (1865) e 'Ubirajara' (1874), by José de Alencar. In other words, to discuss the conciliation between art and nature under the pantheistic perspective of Romanticism as well as its implication in the indianist work, identifying the layers and particularities in the novels of the author. This work will be divided in three parts: in the first one we will elaborate the historical and aesthetical principles of Brazilian Romanticism, believing that inspiration and imagination are the faculties responsible for aestheticizing nature; in the second part we will analyze the organicity of nature in the indianist novels, showing that Alencar was able to build in a unit multiple components of nature - notion based in the Philosophy of Nature, by Friedrich Wilhelm Joseph von Schelling; for the third and last part we will present similarities between the indianist novels and the Homeric epics, as a way to highlight that José de Alencar makes use of epic characters in order to elaborate an essential substance in the primitive world in which his indianist heroes transit. This being said, reputed by many as the founder of an authentic national literature, the author of 'Sonhos d'ouro', however, it goes beyond his role as contributor in the process of our literary and cultural authonomy once he was the one who also revealed in his works a profound aesthetical, historical and philosophical knowledge, which universalize his thinking.